2023
DOI: 10.2196/42523
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Alcohol Refusal Training in Immersive Virtual Reality for Patients With Mild to Borderline Intellectual Disability and Alcohol Use Disorder: Cocreation With Experts in Addiction Care

Abstract: Background People with mild to borderline intellectual disability (MBID; IQ=50-85) are at risk for developing an alcohol use disorder (AUD). One factor contributing to this risk is sensitivity to peer pressure. Hence, tailored trainings are needed to practice alcohol refusal in impacted patients. Immersive virtual reality (IVR) appears promising to engage patients in dialogs with virtual humans, allowing to practice alcohol refusal realistically. However, requirements for such an IVR have not been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Another study [11] that found promising results in reducing blood sugar and serum fructosamine levels using VREPs for treating type 2 diabetes. Participants immersed in VR exercise sessions using IoT-equipped indoor bicycles and VR headsets, experiencing increased muscle mass and greater exercise immersion.…”
Section: Related Workmentioning
confidence: 99%
“…Another study [11] that found promising results in reducing blood sugar and serum fructosamine levels using VREPs for treating type 2 diabetes. Participants immersed in VR exercise sessions using IoT-equipped indoor bicycles and VR headsets, experiencing increased muscle mass and greater exercise immersion.…”
Section: Related Workmentioning
confidence: 99%